Transformations of Sensibility The Phenomenology of Meiji Literature - Kamei, Hideo (Michigan Monograph Series in Japanese Studies, 2020)
First published in Japan in 1983, this book is now a classic in modern Japanese literary studies. Covering an astonishing range of texts from the Meiji period (1868-1912), it presents sophisticated analyses of the ways that experiments in literary language produced multiple new-and sometimes revolutionary-forms of sensibility and subjectivity. Along the way, Kamei Hideo carries on an extended debate with Western theorists such as Saussure, Bakhtin, and Lotman, as well as with such contemporary Japanese critics as Karatani Kojin and Noguchi Takehiko. Transformations of Sensibility deliberately challenges conventional wisdom about the rise of modern literature in Japan and offers highly original close readings of works by such writers as Futabatei Shimei, Tsubouchi Shoyo, Higuchi Ichiyo, and Izumi Kyoka, as well as writers previously ignored by most scholars. It also provides a new critical theorization of the relationship between language and sensibility, one that links the specificity of Meiji literature to broader concerns that transcend the field of Japanese literary studies. Available in English translation for the first time, it includes a new preface by the author and an introduction by the translation editor that explain the theoretical and historical contexts in which the work first appeared.